Pengaruh Current Ratio (CR), Total Asset Turnover (TATO) Dan Debt To Equity Ratio (DER) Terhadap Return On Equity (ROE) Pada Industri Manufaktur Sub Sektor Tekstil Dan Garmen Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2020 - Lina; Pansing, Marcelina Helen; Zega, Thea Putri Amabel; Meliza, Juli (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The purpose of this study was to determine the effect of the Current Ratio, Debt to Equity Ratio and Total Asset Turnover on Return on Equity in case studies of textile and garment sub-sector companies listed on the Indonesia Stock Exchange. Secondary data is used in this study. This research involved 16 companies, namely textile and garment sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2020 research period. The sample used was 8 companies which during the 2017-2020 research period reported their financial data on the Indonesia Stock Exchange (IDX). Purposive sampling was used as the sampling method in this study. The data analysis method used was the classical assumption test, hypothesis testing, multiple regression, F-test and t-test. Based on the results of this study it is known that the Current Ratio and Debt to Equity Ratio have a positive effect on Return on Equity while Total Asset Turnover does not have a significant effect on Return on Equity.